Body weight perception and physical activity level among late adolescents in Kuantan, Pahang : A cross-sectional study - Abd Rahman, Mohd Aizuddin; Jamani, Nurjasmine Aida; Said, Abdul Hadi; Abd. Aziz, Karimah Hanim (2019)
This study measured the association between body weight perception and physical activity level as well as relationship between physical activity level with sociodemographic profiles among late adolescents in Kuantan, Pahang.